A retrospective review of cervical corpectomy: indications, complications and outcome - (:unkn) unknown (SPRINGER WIEN, 2004)
Background. Cervical corpectomy is a common spinal surgery procedure used to decompress the spinal cord in numerous degenerative, traumatic and neoplastic conditions. The aim of this study was to investigate the indications, complications and outcomes in past cervical corpectomy cases at one centre. Method 72 patients who underwent cervical corpectomy between February 1992 and June 2001 were retrospectively investigated. Findings. The indications for this operation were degenerative spondylitic disease (26 cases; 36.1%), trauma (18 cases; 25%), tumour (11 cases; 15.3%), infection (10 cases; 13.9%), and ossification of the posterior longitudinal ligament (7 cases; 9.7%). Thirty-seven patients (51.4%) underwent one-level corpectomy, and 35 (48.6%) underwent two-level corpectomy. Autografts were used in 13 cases (18.1%) and allografts were used in 59 cases (81.9%). Anterior plate-screw fixation was performed in all cases. There were 31 postoperative complications in 15 (20.8%) patients. Twelve of the complications were surgical, 5 were graft-related, 7 were plating-related, and 7 were medical. Solid bony fusion was achieved in 65 (92.9%) of the 70 surviving patients. The mean follow-up time was 23.4 months. An overall favourable outcome was achieved in 88% of cases. Conclusion. The outcomes in this series indicate that cervical corpectomy is an effective method for treating traumatic lesions, degenerative disease, tumours and infectious processes involving the anterior and middle portions of the cervical spine.
Keywords: cervical spine; corpectomy; spinal instrumentation; POSTERIOR LONGITUDINAL LIGAMENT; SPONDYLOTIC MYELOPATHY; ANTERIOR DECOMPRESSION; FOLLOW-UP; INTERVERTEBRAL DISC; INTERBODY FUSION; SPINE SURGERY; RECONSTRUCTION; ARTHRODESIS; PLATES